Translation, cross-cultural adaptation, reliability, and validity of the Turkish version of the Duke Activity Status Index in patients with pulmonary hypertension - R. Mustafaoglu; R. Demir; G.K. Aslan; U.Y. Sinan; M. Zeren; A. Yildiz; M.S. Kucukoglu (Pulmonology, 2023)
Background and objectives: In patients with pulmonary hypertension (PH), shortness of breath, fatigue, chest pain, and syncope limit exercise capacity. Exercise tests are often time-consuming, expensive, and some patients may not be able to perform such procedures and they are also difficult to apply in the studies including large samples.The aim of this study was to translate and culturally adapt the DASI into Turkish and to investigate its reliability and validity in patients with PH. Methods: The final Turkish version of the DASI questionnaire was applied to 109 clinically stable patients with a diagnosis of PH. Exercise capacity of the patients was determined by maximal VO 2 achieved in the 6-minute walk test (6MWT) and quality of life by the EmPHasis-10 questionnaire. Cronbach alpha (internal consistency) was used to assess the questionnaire's reliability. The validity assessment was performed by using Spearman correlation. Results: Internal consistency of the DASI was high (Cronbach's alpha = 0.99) and the test-retest reliability was excellent (ICC = 0.98). Validity was supported by significant correlations of DASI-VO 2 scores with estimated VO 2 (6MWT) scores (r = 0.58, p < 0.0001) and EmPHasis-10 (= −0.62, p < 0.0001). No floor or ceiling effect was present for the questionnaire. Conclusions: The Turkish version of the culturally adapted DASI questionnaire was found to be a valid and reliable assessment tool. It is a rapidly administered, simple-toscore questionnaire for assessing the functional ability of individuals with PH. The use of the DASI to assess exercise capacity in patients with PH may assist researchers and clinicians detecting functional impairment in these patients.